A systematic review of strength and conditioning programmes designed to improve fitness characteristics in golfers - Smith, C. J.; Callister, R.; Lubans, D. R. (Journal of Sports Sciences, 2011)
It has been suggested that conditioning programmes have the potential to improve golf performance through fitness adaptations. The primary aim of this systematic review was to evaluate the effectiveness of conditioning programmes on measures of golf-related fitness and golf performance. Four electronic library databases were searched and the quality of the studies was assessed using criteria adapted from the Consolidated Standard of Reporting Trials statement. Thirteen studies satisfied our criteria for inclusion. Nine studies involved middle-aged to older male recreational golfers and four studies used younger more skilled golfers. Conditioning programmes involved the use of machine weights, free weights, medicine balls, and elastic bands, and most studies included a flexibility component. Most studies assessed changes in fitness characteristics and generally resulted in improvements. All but two of the studies assessed changes in club head speed and reported increases. The findings from this review suggest that strength and conditioning programmes can have a positive effect on the golf swing and fitness characteristics of golfers. The majority of studies in this review evaluated the effects of generic conditioning programmes on fitness characteristics and club head speed. Future studies should investigate the effects of more golf-specific strength and conditioning programmes to improve fitness and overall golf performance.